Impact of pre-appointment contact and short message service alerts in reducing 'Did Not Attend' (DNA) rate on rapid access new patient breast clinics: a DGH perspective - Pasupathy Kiruparan; Nanthesh Kiruparan; Debasish Debnath (BMC, 2020)
Abstract Background Failure to attend the clinic without prior intimation, known as "Did Not Attend" (DNA) is a significant global issue. There have been no published studies attempting to reduce DNA rates in breast clinics. We aimed to assess the impact of contacting patients prior to clinic attendance and Short Message Service (SMS) reminder on DNA rates in rapid access new patient breast clinics, evaluate 'Could Not Attend' (CNA) rate, and explore any correlation between age, sex, clinic days and sessions. Methods Initially, DNAs at the rapid access new patient breast clinic between 01/04/2018 and 31/03/2019 at a district general hospital in the North-West of England was assessed (Cycle 1). Changes were introduced in terms of contacting patients prior to offering appointments, followed by SMS reminders nearer the clinic dates. Subsequently, DNA was reassessed between 01/10/2019 and 31/03/2020 (Cycle 2). Results Following implementation of changes, DNA rate reduced from 8.2 to 4.1% (p < 0.00001). CNA rates were 0.9% (Cycle 1) and 1.1% (Cycle 2) [p = 0.36]. Evening clinics had the lowest DNA rates throughout. DNA patients in cycle 2 were significantly older than those in cycle 1 (p = 0.002). Conclusions Contacting patients prior to clinic appointments and sending SMS reminders helped reduce DNA rates significantly in rapid access new patient breast clinics. Scheduling clinic sessions with least DNA rates, such as evening clinics, should be contemplated. One should be cautious of mobile phone technology that conveys SMS, which can potentially disadvantage the older age group. This model could be considered across the board to improve DNA rates.